2009
DOI: 10.1021/ic9019487
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatomic Deltahedral Zintl Ions of Group 14 and their Alkenylation

Abstract: Reported is the synthesis of Ge(9-x)Sn(x) heteroatomic deltahedral Zintl ions and their alkenylation by reactions with alkynes. The nine-atom clusters are made either by extraction from mixed Ge/Sn precursors with nominal composition K(4)Ge(9-x)Sn(x) or by dissolution of mixtures of the corresponding binary precursors K(4)Ge(9) and K(4)Sn(9) in solvents with high dielectric constants such as DMF, DMSO, and acetonitrile. Reactions of the heteroatomic clusters with alkynes such as Me(3)SiC[triple bond]CSiMe(3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 76 publications
3
33
0
3
Order By: Relevance
“…[23,24] The shape of the cluster is very similar to the known analogous clusters functionalized by one or two main-group organometallic fragments or organic groups. [21,22,24,26,27] The mesityl group in 1a is connected to Ge1, which is part of the open square of the cluster. The Ge-C distance of 2.03(1) Å is in agreement with the Ge-C bond length of 1.94(1) Å in [Ph-Ge 9 -SbPh 2 ] 2-.…”
Section: Introductionsupporting
confidence: 53%
“…[23,24] The shape of the cluster is very similar to the known analogous clusters functionalized by one or two main-group organometallic fragments or organic groups. [21,22,24,26,27] The mesityl group in 1a is connected to Ge1, which is part of the open square of the cluster. The Ge-C distance of 2.03(1) Å is in agreement with the Ge-C bond length of 1.94(1) Å in [Ph-Ge 9 -SbPh 2 ] 2-.…”
Section: Introductionsupporting
confidence: 53%
“…To examine the stability of the Ge-C core, crystals of 1 were dissolved in a solution of DMF, and ESMS clearly showed that the sp 3 hybridized carbon cluster core remained intact even after ionization (see Figure 2). In the positive ion mode, several cluster species were characterized by their isotope pattern [18,19,34,41,42]. The clusters retained the mass of the core Ge4C with several halides (m/z = CCl11Ge4 + (691), CBrCl10Ge4 + (737), CBr2Cl9Ge4 + (781), CBr3Cl8Ge4 + (825), and CBr4Cl7Ge4 + (870)), thus supporting the stability of compound 1.…”
Section: Synthesis Results and Discussionmentioning
confidence: 82%
“…The clusters retained the mass of the core Ge4C with several halides (m/z = CCl11Ge4 + (691), CBrCl10Ge4 + (737), CBr2Cl9Ge4 + (781), CBr3Cl8Ge4 + (825), and CBr4Cl7Ge4 + (870)), thus supporting the stability of compound 1. Such multi metal-chalcogenide clusters, with partial oxidation caused by the electric ESMS field, is a common phenomenon when being ionized [41,42]. However, evidence of the intact core was unexpected as the Ge-Cl (356 kJ/mol) and Ge-Br (276 kJ/mol) have stronger bond dissociation energies than the Ge-C (255 kJ/mol) bond.…”
Section: Synthesis Results and Discussionmentioning
confidence: 99%
“…We have shown before that the alkenylation of Ge9 clusters by a reaction with alkynes is a nucleophilic addition of the clusters to the triple bond: 55,57 K4Ge9 + 2TMS-C≡C-TMS + 6H2NR → [K]2[Ge9-(CH=CH2)2] + 4TMS-NHR + 2K-NHR where H2NR represents the solvent ethylenediamine. In the reaction, one of the germanium lone pairs attacks the empty π* orbitals of the triple bond and supplies a pair of electrons to it.…”
Section: Running Es-ms Of Reaction Solutionmentioning
confidence: 99%
“…[3][4][5][6] Notable milestones are the oxidative coupling of Ge9 4-clusters to oligomers and infinite chains, 7-19 their metallation, [14][15][16][20][21][22][23][24][25] capping by transition-metal organometallic fragments, 26-34 insertion of a transition-metal atom at the center of the cluster which is sometimes combined with capping and oligomerization, 35-47 addition of main-group organometallic fragments as exo-bonded substituents, 48-50 and functionalization with various organic residues by reactions with organic halides and alkynes. [51][52][53][54][55][56][57][58] This latter development of attaching organic fragments directly to the clusters has opened up a new field, namely organo-Zintl chemistry, that is potentially fertile for further synthetic explorations, and it is the step-by-step procedure for the synthesis of germanium-divinyl clusters described herein. The initial steps outline the synthesis of an intermetallic precursor of K4Ge9 from which the Ge9 4-clusters are extracted later in solution.…”
Section: Introductionmentioning
confidence: 99%